The Effect of Family Support on Medication Adherence in Schizophrenic Patients with Violence Behaviors - Sarbrum, Aroonkamole; Upasen, Ratchaneekorn (Journal of The Royal Thai Army Nurses, 2024)
The quasi-experimental research which was conducted as pretest-posttest control group design, aimed; 1) to compare medication adherence behaviors in schizophrenic patients with violence before and after receiving a family support program, and 2) to compare between the groups receiving the family support program and regular nursing care. The sample group was schizophrenic patients with violence who came to receive services at the inpatient department, Prasrimahabhodi Psychiatrict Hospital. They were 40 qualified patients coming along with family. They were randomly assigned to an experimental and Control group of 20 participants each. The research instruments included 1) Family Support Program, 2) Personal Data Questionnaire, 3) Brief Psychiatric Rating Scale 4) Medication Adherence Scale, and 5) Social Support Scale; all of which have passed the content validity test from 5 experts with the alpha-Cronbrach reliability coefficient of .85 and .89, respectively. The data were subsequently analyzed using means, a standard deviation, and t-test statistics. The results: The medication adherence behavior of schizophrenic patients with violence in was .05 statistically significant and was shown to be higher than before receiving the family support program. The schizophrenic patients with violence who were in the family support program group was shown to be .05 statistically significant in medication adherence behaviors, higher than its counterpart.